Notes to Philosophy 167: Class 5 -- Other Developments in Astronomy from 1609 to 1642 -- Part 5. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Synopsis: Galileo's Telescopes: Design and Limitations -- Further Telescopic Discoveries: 1610-1620; Generally corresponds to the video segment: Class 5, Part 5.